Community pharmacies as sites of adult vaccination: A systematic review. Issue 12 (1st December 2016) - Burson, Randall C.; Buttenheim, Alison M.; Armstrong, Allison; Feemster, Kristen A.
ABSTRACT: Vaccine-preventable deaths among adults remain a major public health concern, despite continued efforts to increase vaccination rates in this population. Alternative approaches to immunization delivery may help address under-vaccination among adults. This systematic review assesses the feasibility, acceptability, and effectiveness of community pharmacies as sites for adult vaccination. We searched 5 electronic databases (PubMed, EMBASE, Scopus, Cochrane, LILACS) for studies published prior to June 2016 and identified 47 relevant articles. We found that pharmacy-based immunization services (PBIS) have been facilitated by state regulatory changes and training programs that allow pharmacists to directly provide vaccinations. These services are widely accepted by both patients and pharmacy staff, and are capable of improving access and increasing vaccination rates. However, political and organizational barriers limit the feasibility and effectiveness of vaccine delivery in pharmacies. These studies provide evidence to inform policy and organizational efforts that promote the efficacy and sustainability of PBIS.